Microbiota Properties and Texture of Rice Flour Bread with Pineapple Starter - Icca Ratna Danila; Rini Yanti; Dian Anggraini Suroto (Journal of Applied Agricultural Science and Technology, 2023)
Changing the ingredients also can change the properties of the bread. In this study, bread was made using rice flour and sourdough. Sourdough with Lactic Acid Bacteria (LAB) and yeast can also be added with pineapple starter to help microbiota growth. The study aimed to determine the amount of microbiota produced from sourdough with pineapple addition and its effect on the texture of rice flour bread. Pineapples with water and sugar were fermented to make pineapple starter. Pineapple starter is then used in sourdough making and fermented around 3-6 days. The mature sourdough was used in bread making. The addition of pineapple, in the form of a starter, made the pineapple sourdough (PS) have lower pH and higher titratable acidity (TA), total Lactic Acid Bacteria (LAB), and total yeast than sourdough without the addition of pineapple starter or wheat sourdough (WS). The pH and TA of PS at the peak were 3.25 and 2.67 mL of NaOH. The total LAB of PS at the peak was 9.27 Log CFU/g, and the total yeast was 9.30 Log CFU/g. PS reached its peak on the third day, while wheat sourdough (WS) reached it on the sixth day. The pineapple sourdough bread (PSB) had the lowest specific volume, and the highest texture properties compared to control bread (CB) and wheat sourdough bread (WSB), but there is no significance different. The addition of pineapple starter can fasten the fermentation time of sourdough and made the bread less brittle than CB.